Ethical responsibilities toward indirect and collateral participants in pragmatic clinical trials. (October 2015) - Smalley, Jaye Bea; Merritt, Maria W; Al-Khatib, Sana M; McCall, Debbe; Staman, Karen L; Stepnowsky, Carl
Pragmatic clinical trials are designed to inform decision makers about the benefits, burdens, and risks of health interventions in real-world settings. Pragmatic clinical trials often use for research purposes data collected in the course of clinical practice. The distinctive features of pragmatic clinical trials demand fresh thinking about what is required to act properly toward people affected by their conduct, in ways that go beyond ensuring the protection of rights and welfare for "human research subjects" under conventional research ethics regulations. To stimulate such work, we propose to distinguish among categories of research participants in pragmatic clinical trials as follows: Direct participants: (1) individuals being directly intervened upon and/or (2) individuals from whom personal identifiable data are being collected for the purposes of the pragmatic clinical trial. Indirect participants: individuals who are (1) not identified as direct participants and (2) whose rights and welfare may be affected by the intervention through their routine exposure to the environment in which the intervention is being deployed. Collateral participants: patient groups and other stakeholder communities who may be otherwise affected by the occurrence and findings of the pragmatic clinical trial. We illustrate these distinctions with case examples and discuss the distinctive responsibilities of researchers and pragmatic clinical trial leadership toward each type of participant. We suggest that pragmatic clinical trial investigators, institutional review boards, health systems leaders, and others engaged in the research enterprise work together to identify these participants. For indirect participants, risks and benefits to which they are exposed should be weighed to ensure that their rights and welfare are protected accordingly, and communication strategies should be considered to help them make well-informed decisions. Collateral participants could provide input on the design, planning, and conduct of a pragmatic clinical trial and offer insights regarding the best way to communicate the trial's results to their constituencies.